Investigation of the Photocatalytic Activity of Carbon Doped TiO2 for Photodegration of Methylene Blue (Journal of Scientific Research, 2024)
Nanoparticles of pure TiO2 and carbon doped TiO2 (at various concentrations 1, 2, 3 and 4 %) were synthesised by Sol gel method using titanium butoxide and glucose as a precursors for Titanium dioxide and carbon respectively. The samples were calcinated at 500 °C. Photocatalytic activity of the samples was tested for photodegradation of methylene blue dye. Morphological and elemental analysis of the samples were carried out using a scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDAX), X-ray diffraction and micro-raman spectroscopy while for optical characterization UV-Vis diffuse reflectance spectra were employed.  Results of all samples indicated crystallite growth in a tetragonal structure with the variation in crystallite size in the range 9 nm to 12.6 nm with increase in the concentration of dopant in TiO2. Diffused reflectance spectroscopy (DRS) analysis indicated that the band gap of all doped TiO2 nanoparticles is lesser than that of the pure TiO2 whereas 4C-TiO2 showed smallest band gap (2.98 eV). The maximum photocatalytic activity was observed with 4C-TiO2 among all the samples.